Public Attitudes Toward Precision Medicine: A Nationwide Survey on Developing a National Cohort Program for Citizen Participation in the Republic of Korea - Kim, Hannah; Kim, Hye Ryun; Kim, Sumin; Kim, Eugene; Kim, So Yoon; Park, Hyun-Young (Frontiers in Genetics, 2020)
This nation-wide survey was conducted to examine the social interest for and attitude toward establishing the citizen participation cohort design and the directions of the “Resource Collection Project for Precision Medicine Research” among Korean adults before the project will proceed. The demographic framework of this survey was established based on the residents of Korea following the statistical standard of the Ministry of the Interior and Safety. An online survey was carried out using web panels between May 14, 2018 and May 23, 2018. Sampling was performed using a simple proportional allocation method considering region, gender, and age. The survey received very high support (94.5%) and the intention to participate was as high as 83.5%. Respondents were very positive to provide each types of samples and information to the study (84.5~89.9%). Respondents wanted to receive health information (80.2%), monetary compensation (51.4%) and smart devices (41.3%). Most participants responded it was appropriate to carry out the project at governmental institute (66.9%). Respondents also had a positive attitude toward only the government researchers who run the project for sampling and sharing their information (88.0%). However, the survey participants expressed concerns about time consuming or hassle (38.1%), privacy breaches (33.6%) and the lack of returning benefits if participation (25.1%). Participants had a negative attitude toward sharing their data to various researchers.